2017
DOI: 10.1017/s0142716416000473
|View full text |Cite
|
Sign up to set email alerts
|

Exploring minority language input sources as means of supporting the early development of second language vocabulary and grammar

Abstract: Exposure to a minority language is largely limited in terms of frequency, and often delivered by nonnative speakers in certain domains. This study aimed to evaluate the effectiveness of two types of native-language input sources (story telling and minority language children's television) in providing 4- and 5-year-old native English-speaking children with beginning awareness of Welsh. Results revealed that exposure to Welsh via television programs was equally as beneficial, if not more so in some cases, as lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 82 publications
(111 reference statements)
0
4
0
Order By: Relevance
“…For example, perhaps children are more likely to engage in imaginative play with older siblings compared to mothers. Indeed, a crucial role for interactive language input has been suggested in previous studies (e.g., Sorenson Duncan & Paradis 2019; Williams & Thomas, 2017). Accordingly, future research which considers the type of interaction, the L2 proficiency, and potential age-related differences in how siblings interact is needed to detail the way in which input from siblings influences L2 acquisition.…”
Section: Discussionmentioning
confidence: 84%
“…For example, perhaps children are more likely to engage in imaginative play with older siblings compared to mothers. Indeed, a crucial role for interactive language input has been suggested in previous studies (e.g., Sorenson Duncan & Paradis 2019; Williams & Thomas, 2017). Accordingly, future research which considers the type of interaction, the L2 proficiency, and potential age-related differences in how siblings interact is needed to detail the way in which input from siblings influences L2 acquisition.…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, children who engaged in regular co-reading activities with their parents showed larger gains in receptive vocabulary skills than those whose parents read less often to them during lockdown, but no significant gains in expressive vocabulary (Kartushina et al, 2022). Williams and Thomas (2017) have also shown how live interactions with an interlocutor during television viewing in class supports language development among young L2 pupils more so than reading a story out loud to the class or allowing children to passively engage with watching television. Beyond the early years, social interaction has been shown to aid the development of an L2 among adult learners (Verga & Kotz, 2013), regardless of proficiency levels within communicative pairs (Watanabe & Swain, 2007).…”
Section: Key Factors In the Development Of Language Competencementioning
confidence: 94%
“…These social interactions facilitate infants' mapping of words onto objects through joint attention (Baldwin, 2000), leading to the development of a Theory of Mind (Sodian & Kristen-Antonow, 2015), a skill that can facilitate the later development of cognitive reasoning (De Villiers, 2007). Joint attention is often facilitated through co-reading (Farrant & Zubrick, 2012), and co-reading practices are key precursors to the later development of vocabulary, problem-solving, and reading skills (see Williams & Thomas, 2017 for an overview). Interactions with a communicative partner, such as coreading, has clear links with gains in expressive language development, whereas passive engagement with language (spoken or written -e.g., listening to a video recording) contributes to the continuous development of receptive language skills.…”
Section: Key Factors In the Development Of Language Competencementioning
confidence: 99%
“…Instead of focusing on the caparison between monolingual and bilingual infants' linguistic development, more studies have suggested that it is more crucial to consider the effect of other environmental factors. For example, researches identified the amount of language input plays a substantial role in affecting young bilinguals' both vocabulary and grammatical abilities [8,9,10].…”
Section: Language Developmentmentioning
confidence: 99%